Speculative heritage: Evaluating how emergent technology can be used to assess our understanding of heritage - Charles, Tadhg (My University, 2023)
In this thesis I explore what I perceive to be one of the main difficulties involved in architectural heritage practice. Our current approach towards preservation prioritises qualities in an inequitable manner and this results from a misconception about the singular correct interpretation of a building’s essential character. In conventional historical procedure there is a prevalent concept that the best action is to preserve structures in stasis. This interpretation posits the idea that an architectural construct occupies a single state of correct intelligibility. I believe that a historical edifice is never one thing, it always embodies multiple readings simultaneously. Using emergent technology, I highlight the subjective differences that proliferate in the individual comprehensions of a building’s form. By contrasting subjective interpretations of the monuments against objective recordings I will highlight what lies at the centre of proclamations about their correct conservation. The reason for this investigation is to critically consider how we understand and engage with the physical manifestations of our past. It is important to re-evaluate how we work with this information given the accelerated rate of change caused by both climatic and social conditions which are resulting in the irreparable loss of countless artifacts. Acknowledging the delicate finite quality of historical edifices, we should contemplate and simulate potential scenarios for legacy structures whilst reflecting on our own phenomenological attachments. It is my conjecture that emergent technology allows for a new and exciting means of exploring and questioning our actions while hypothesizing possibilities which traditionally would be considered contentious. What qualities do we aim to preserve and how might this be done in the most suitable manner? If all understanding of heritage is a personalised filter can technology allow for the sharing of this perspective. I propose a speculative approach that asks what is embedded in built heritage and our interpretation of it. I want to see how possible it is to manifest subjectivity through emergent technology to allow for a more representative and inclusive demonstration of our historical narrative and how it relates to heritage.
Keywords: Speculative heritage, Heritage practice, Preservation; Emergent technology, Simulations, Legacy structures; Phenomenological attachments, entanglement, Replicas; Authenticity and Composition of memory identity, subjectivity, objectivity